Associations between body composition, macronutrient intake, and physical fitness in adolescent swimmers - Gunawan, Renaldy Carlos; Pratama, Satwika Arya (UIR Press, 2025)
Background: Physical fitness plays a key role in the performance of adolescent swimmers. However, gaps remain in understanding how body composition and macronutrient intake jointly influence fitness when accounting for individual variability. Research Objectives: This study examines the correlation between macronutrients and body composition with physical fitness in adolescent swimming athletes from Bojonegoro. Methods: A cross-sectional study was conducted with 41 adolescent swimmers. Macronutrient intake was assessed using a Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), body composition via Bioelectrical Impedance Analysis (BIA), and physical fitness through the Multistage Fitness Test. Spearman correlation and multiple linear regression were used to evaluate associations, adjusting for age, sex, weight, and height. Findings/Results: Physical fitness was positively correlated with skeletal muscle mass and intake of carbohydrates, protein, and fat (p < 0.05), and negatively correlated with total body fat. Demographic variables (age, sex, height) explained 42.7% of physical fitness variability (adjusted R² = 0.427, p < 0.001). Including exercise activities, body composition, and nutrient variables increased R² to 0.597, but the full model was not statistically significant (adjusted R² = 0.404, p = 0.803). Conclusion: Body composition and macronutrient intake are associated with physical fitness, but demographic factors remain the strongest predictors. Individualized training and dietary strategies may support performance optimization in adolescent athletes. Future studies with larger sample sizes and longitudinal designs are recommended to confirm and extend these findings.